The Influence of ROA, ROE, CR, and DER, on Stock Returns of Non-Banking Companies Listed on the LQ-45 Index and the Sri-Kehati Index on the Indonesian Stock Exchange 2019–2023 - Santoso, Herry (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2024)
When investing, investors really need certain indicators to assess the company whose shares will be purchased. These indicators are analysis of financial ratios such as Profitability Ratios where only two ratios are taken, namely Return on Assets (ROA) and Return on Equity (ROE). Apart from the Profitability Ratio, the Liquidity Ratio, namely the Current Ratio (CR) and the Solvency Ratio, namely the Debt to Equity Ratio (DER) as an indicator of the health of a company. In this research, the author uses panel data regression analysis which consists of time series data and also cross-section data, where the independent variable is regressed on the dependent variable, namely stock returns. The author chose the independent variables using Profitability Ratios where the author chose from these ratios for this research the Return on Assets (ROA) Ratio and the Return on Equity (ROE) Ratio. Meanwhile, for the Liquidity Ratio, the Current Ratio (CR) is chosen and for the Solvency Ratio, the Debt to Equity Ratio (DER). The independent variables consisting of ROA, ROE, and DER have a probability value greater than the significance level of 5% so this can be interpreted as meaning that the independent variables ROA, ROE, and DER have no influence on the dependent variable, namely stock returns. However, for CR, which is also an independent variable, the probability value is 0.0008, which is smaller than the 5% significance level, so it can be concluded that CR has an effect on the dependent variable.